Refinement of Multiparameters Overrelaxation (RMPOR) Method - Gashaye Dessalew; Tesfaye Kebede; Gurju Awgichew; Assaye Walelign (Journal of Mathematics)
In this paper, we present refinement of multiparameters overrelaxation (RMPOR) method which is used to solve the linear system of equations. We investigate its convergence properties for different matrices such as strictly diagonally dominant matrix, symmetric positive definite matrix, and M-matrix. The proposed method minimizes the number of iterations as compared with the multiparameter overrelaxation method. Its spectral radius is also minimum. To show the efficiency of the proposed method, we prove some theorems and take some numerical examples.